A SHORT NOTE ON THE CHROMOSSOMES OF PHLUGIS (ORTHOPTERA, LISTROSCELIDAE) - Piza Jr, S. de Toledo (REVISTA DE AGRICULTURA, 2016)
A SHORT NOTE ON THE CHROMOSSOMES OF PHLUGIS (ORTHOPTERA, LISTROSCELIDAE)